2015
DOI: 10.1108/cdi-12-2014-0158
|View full text |Cite
|
Sign up to set email alerts
|

The influence of transformational leadership on followers’ affective commitment

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 89 publications
6
38
0
3
Order By: Relevance
“…Their results indicate that transformational leadership positively affects perceived organizational support and validated that transformational leadership has a strong and positive impact on pos. This result was consistent with Stinglhamber, Marique, Caesens, Hanin, and De-Zanet (2015), who examined the impact of transformational leadership on followers perceived organizational support in a sample of 287 employees of a water producer organization. The results of this study show that when employees strongly identify their supervisor with the organization, a transformational leadership style is positively related to pos.…”
Section: Final Considerationssupporting
confidence: 88%
“…Their results indicate that transformational leadership positively affects perceived organizational support and validated that transformational leadership has a strong and positive impact on pos. This result was consistent with Stinglhamber, Marique, Caesens, Hanin, and De-Zanet (2015), who examined the impact of transformational leadership on followers perceived organizational support in a sample of 287 employees of a water producer organization. The results of this study show that when employees strongly identify their supervisor with the organization, a transformational leadership style is positively related to pos.…”
Section: Final Considerationssupporting
confidence: 88%
“…Meantime, Research by Q Yinan, M Tang, M Zhang (2014) showed supply chain planning and corporate coordination are positively relat ed to mass customization, which are conducive to achieving better customer services as well as improving front-line sales staffs' service quality [23]. Previous studies showed that transformational leadership is positively related to many positive outcomes such as job satisfaction [12] and organizational commitment [16]. Meanwhile, job satisfaction and organizational commitment have significant influence on employees' service quality in high-contact service industries [17].When employees feel that they are a part of the organization and identify with the goals set by the organization, they will fulfill their responsibilities and obligations in good faith such as improve service quality, rather than be forced to do so.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Transformational leadership displays a class of behaviors enacted by a leader spanning four dimensions: idealized influence-the leader causes followers to trust, admire, and identify with them; inspirational motivation-the leader articulates a compelling vision of the future that inspires followers; intellectual stimulation-the leader encourages followers to take risks; individualized consideration-the leader tends to employees' individual needs [9]. Many studies have shown that transformational leadership can improve employees' job satisfaction [12], employees' well-being [13], organizational citizenship behaviors [14], task performace [15]and organizational commitment [16]. Meantime, positive working outcomes such as job satisfaction and organizational commitment have significant influence on employees' service quality in high-contact service industries [17].…”
Section: Introductionmentioning
confidence: 99%
“…Bono et al (2007) provide compelling evidence that leadership behaviors have an influence on employees' optimism and enthusiasm. Transformational leadership as a whole construct has been related to team affective states, satisfaction, and affective commitment (Chi, Chung, & Tsai, 2011;Chi & Huang, 2014;Stinglhamber, Marique, Caesens, Hanin, & De Zanet, 2015;To, Tse, & Ashkanasy, 2015), and positive affect has been suggested as a relevant boundary condition for the influence of transformational leadership on effectiveness and behaviors (Gilmore, Hu, Wei, Tetrick, & Zaccaro, 2012). Hernandez-Baeza et al (2009), for example, found that transformational leadership (i.e., charisma) infuse positive affect in their followers.…”
Section: Discussionmentioning
confidence: 99%
“…Hobman et al (2011) reported that intellectual stimulation of the leader had a significant positive relationship with satisfaction and performance mediated by members' identification with the leader. Additionally, transformational leadership as a whole and its sub-dimension has been related to affective commitment (Rafferty & Griffin, 2004;Stinglhamber et al, 2015). In a study conducted by Rafferty and Griffin (2004), although they initially hypothesized a relationship between vision and affective commitment, results showed that only intellectual stimulation and inspirational communication were statistically related to this outcome.…”
Section: Discussionmentioning
confidence: 99%